2012
DOI: 10.1002/hbm.22072
|View full text |Cite
|
Sign up to set email alerts
|

The cortical control of cycling exercise in stroke patients: An fNIRS study

Abstract: Stroke survivors suffering from deficits in motor control typically have limited functional abilities, which could result in poor quality of life. Cycling exercise is a common training paradigm for restoring locomotion rhythm in patients. The provision of speed feedback has been used to facilitate the learning of controlled cycling performance and the neuromuscular control of the affected leg. However, the central mechanism for motor relearning of active and passive pedaling motions in stroke patients has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…These findings suggested that the unaffected premotor activation may play a compensative role in stroke recovery. 39 However, the pattern of functional reorganization is not uniform and may vary with the type of lesion or symptom of each patient. In patients with stroke with ataxia, gait-related activation in the medial SMC is comparable to that of healthy subjects.…”
Section: Neural Mechanism For Gait Controlmentioning
confidence: 99%
“…These findings suggested that the unaffected premotor activation may play a compensative role in stroke recovery. 39 However, the pattern of functional reorganization is not uniform and may vary with the type of lesion or symptom of each patient. In patients with stroke with ataxia, gait-related activation in the medial SMC is comparable to that of healthy subjects.…”
Section: Neural Mechanism For Gait Controlmentioning
confidence: 99%
“…The system can help the paretic hand perform hand grasp and release according to a subject's voluntary motor intention detected by EMG signal from the residual muscles of the affected side, meanwhile the subject also can conduct the whole upper limb movement at the same time, such as reaching. Voluntary physical experience is a major modulator for the neural plasticity in the nervous system after stroke (Jiang et al, 2013;Lin et al, 2012Lin et al, , 2009Miyai et al, 2006;Takeuchi and Izumi, 2013;Ding et al, 2011). Involvement of voluntary efforts during rehabilitation training has been found to be more effective than those only with passive motions (Volpe et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Reorganization of surviving neural networks in the brain rather than repair of the damaged tissue is the key for motor functional restoration after stroke, which depends on repeated and intensive physical practice of the paretic limb on the motor skills to be restored (Lin et al, 2012(Lin et al, , 2009Miyai et al, 2006;Murata et al, 2006;Dijkhuizen et al, 2012;Takeuchi and Izumi, 2013). Therefore, physical training related to daily tasks has been widely adopted in post-stroke rehabilitation (Tan et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…A frequency-domain near-infrared spectroscopy (FD-NIRS) system was used in stroke patients to detect the hemodynamic changes resulting from neuronal activity during the pedaling exercise from the bilateral SMCs, SMAs, and PMCs. 55 The results showed that PC had a cortical activation pattern similar to that observed during active cycling without feedback but with a smaller intensity in the SMC of the unaffected hemisphere.…”
Section: Discussionmentioning
confidence: 60%